The Effects of Raw Material Ratio and Calorific Value on Gasification Rate from Co-Gasification of Coal and Biomass (Bagasse) - Kurniansyah, Muhammad Harry; Hasan, Abu; Syari, Aida (Jurnal Bahan Alam Terbarukan, 2023)
To reduce greenhouse gas pollution by 29% in 2030 and actively fight climate change, Indonesia uses biomass as an alternative energy which can be combined with coal. Bagasse is a relatively abundant biomass that has not been effectively utilized. Bagasse can be used as a more effective alternative energy source if it is processed with co-gasification, which is the conversion of solid fuel into gas from two different fuel materials at the same time to produce syngas. The characteristics of biomass and coal co-gasification are closely linked to reactor type and gasification parameters such as temperature, gasifying agent, and mass ratio. The composition of the produced syngas changes depending on the calorific value of the coal used and the raw material ratio. The amount of syngas produced rises in direct proportion to the amount of biomass, and the quantity of air supplied causes complete combustion, so the syngas content decreases. The impact of the calorific value of the coal used, as well as variations in the ratio of the composition of coal and bagasse, on the supply of oxygen in downdraft type gasification equipment is investigated in this study. Bagasse characteristics identified by proximate and ultimate analysis indicate that this biomass can be used as an alternative source of renewable energy. The co-gasification process with 100% coal raw material has the highest temperature and the longest time; the co-gasification process with 100% sugarcane bagasse raw material has the lowest temperature and the shortest time; and the duration of the flame produced in syngas ranges from 5-6 minutes. The 25% bagasse and 75% coal ratio provided the fastest high temperature in this testing, making it more efficient. The calorific value of coal and biomass determines combustion efficiency, with 5300 cal/gr coal producing heat that lasts longer than 3800 cal/gr and 4500 cal/gr.